Transformaciones en el empleo y el territorio: el caso San Luis - Bussetti, Mónica (2007)
The economic and social processes produce territorial effects. Every territory deals with these processes in specific and distinctive ways, according with its productive history and the practices and strategies of the social agents involved in the management of changes. Though the processes of change that take place in every territory are set in some global trends that contextualize the diverse answers, in some cases the answers only can be adequately understood taking in count the distinctive characteristics in each territory. In San Luis' province, along the last two decades, the production of the territory was sealed by the transformations happened when some national plans of industrial promotion started. This affected all the dimensions of the social life. In fact, this new situation not only changed the productive orientation of the province, but struck also on individual and familiar behaviours that, in an aggregate level, determine the level and fluctuations of demographic dynamics. Particularly, a population displacement happened towards the industrial parks of the principal urban centers of the province and, as a consequence, rural areas lost population. Hereby, the industrialization had a new territorial expression, which shaped new landscapes of segregation and new forms of exclusion. In the middle of the decade of 1990, promotional benefits ceased, and a series of public politics, directed promote new productive profiles, generated new impacts on territorial organization. This work proposes an analysis of these processes, taking specially in count that transformations in employment and territory are overawed mutually. In another words: the transformations in territorial competitiveness express on problems of employment and labour market, and the changes in the employment generate strong changes in the perspective of a territorial area.